Optimizing Hydrogen Binding on Ru Sites with RuCo Alloy Nanosheets for Efficient Alkaline Hydrogen Evolution. (7th December 2021) - Cai, Chao; Liu, Kang; Zhu, Yuanmin; Li, Pengcheng; Wang, Qiyou; Liu, Bao; Chen, Shanyong; Li, Huangjingwei; Zhu, Li; Li, Hongmei; Fu, Junwei; Chen, Yu; et al.
Abstract: Ruthenium (Ru)‐based catalysts, with considerable performance and desirable cost, are becoming highly interesting candidates to replace platinum (Pt) in the alkaline hydrogen evolution reaction (HER). The hydrogen binding at Ru sites (Ru−H) is an important factor limiting the HER activity. Herein, density functional theory (DFT) simulations show that the essence of Ru−H binding energy is the strong interaction between the 4 d z 2 orbital of Ru and the 1s orbital of H. The charge transfer between Ru sites and substrates (Co and Ni) causes the appropriate downward shift of the 4 d z 2 ‐band center of Ru, which results in a Gibbs free energy of 0.022 eV for H* in the RuCo system, much lower than the 0.133 eV in the pure Ru system. This theoretical prediction has been experimentally confirmed using RuCo alloy‐nanosheets (RuCo ANSs). They were prepared via a fast co‐precipitation method followed with a mild electrochemical reduction. Structure characterizations reveal that the Ru atoms are embedded into the Co substrate as isolated active sites with a planar symmetric and Z‐direction asymmetric coordination structure, obtaining an optimal 4 d z 2 modulated electronic structure. Hydrogen sensor and temperature program desorption (TPD) tests demonstrate the enhanced Ru−H interactions in RuCo ANSs compared to those in pure Ru nanoparticles. As a result, the RuCo ANSs reach an ultra‐low overpotential of 10 mV at 10 mA cm −2 and a Tafel slope of 20.6 mV dec −1 in 1 M KOH, outperforming that of the commercial Pt/C. This holistic work provides a new insight to promote alkaline HER by optimizing the metal‐H binding energy of active sites. Abstract : Optimizing Ru−H adsorption/desorption efficiency, via adjusting the Ru 4 d z 2 orbital in RuCo alloy‐nanosheets, enables highly promoted alkaline hydrogen evolution reaction. This optimized adsorption/desorption efficiency is demonstrated by the hydrogen sensor and temperature programmed desorption experiments. The RuCo alloy‐nanosheets possess a record low overpotential of 10 mV at 10 mA cm −2, superior to the commercial Pt/C and Ru/C.